Spinal muscular atrophy with lower limbs phenotype: clinical and genetic description of novel mutation in the DYNC1H1 gene - E. L. Dadali; S. S. Nikitin; F. A. Konovalov; I. A. Akimova; S. A. Korostelev (Нервно-мышечные болезни, 2018)
Background. Spinal muscle atrophies (SMA) are a group of diverse heterogenous diseases caused by mutations in several dozens of genes. A rare form of autosomal dominant SMA predominantly affects muscles of the lower extremities.The study objective is to describe clinical and genetic characteristics of Russia-living patients with SMA predominantly affecting muscles of the lower extremities caused by the DYNC1H1 gene mutation discovered by next-generation exome sequencing.Materials and methods. To diagnose the syndrome a complex of examination techniques was used: genealogical analysis, neurological examination, electromyography, and DNA diagnostics. Changes in the nucleotide sequence in the probands and their parents identified with massive parallel sequencing were studied using direct automatic sequencing with oligonucleotide primers.Results. Five (5) patients from 4 families with heterozygous mutations in the DYNC1H1 gene were identified. In the patients, one type of SMA predominantly affecting the lower extremities was assumed. Prior to exome sequencing, all patients were monitored for myelodysplasia diagnosis, and magnetic resonance imaging of the spine has showed protrusions and/or spondylolisthesis of the lumbar spine in 4 of the patients. The obtained results can demonstrate both hyperdiagnosis and that spinal pathology is one of the characteristic symptoms of SMA predominantly affecting the lower extremities.Conclusion. The obtained results allow to make an assumption about a wide range of clinical polymorphisms in patients with mutations of the DYNC1H1 gene. Apart from typical clinical manifestations of SMA predominantly affecting the lower extremities, patients can be diagnosed with hereditary motor and sensory neuropathy 2, myelodysplasia, and congenital arthrogryposis which has to be taken into account during diagnostic search.